2014
DOI: 10.1007/s10935-014-0380-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of the keepin’ it REAL Model Program in Mexico: Substance Use Trajectories of Guadalajara Middle School Students

Abstract: In the face of rising rates of substance use among Mexican youth and rapidly narrowing gender differences in use, substance use prevention is an increasingly urgent priority for Mexico. Prevention interventions have been implemented in Mexico but few have been rigorously evaluated for effectiveness. This article presents the long term effects of a Mexico-based pilot study to test the feasibility of a linguistically specific (Mexican Spanish) adapted version of keepin’ it REAL, a school-based substance abuse pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 26 publications
0
25
0
4
Order By: Relevance
“…The researchers found that the programme reduced the frequency that alcohol (ES ¼ À0.22, SE ¼ 0.09) and cigarettes (ES ¼ À0.18, ES ¼ 0.09) were used and the amount of cigarettes used (ES ¼ À0.15, SE ¼ 0.08). The 2015 study (Marsiglia, Kulis, Booth, Nuño-Gutierrez, & Robbins, 2015) reported on the same data set but with access to all three waves. The researchers reported that the KiR programme retarded the growth of alcohol use frequency for females and marijuana use for males, with no effect on tobacco use.…”
Section: Mexican Middle School Adaptationsmentioning
confidence: 99%
“…The researchers found that the programme reduced the frequency that alcohol (ES ¼ À0.22, SE ¼ 0.09) and cigarettes (ES ¼ À0.18, ES ¼ 0.09) were used and the amount of cigarettes used (ES ¼ À0.15, SE ¼ 0.08). The 2015 study (Marsiglia, Kulis, Booth, Nuño-Gutierrez, & Robbins, 2015) reported on the same data set but with access to all three waves. The researchers reported that the KiR programme retarded the growth of alcohol use frequency for females and marijuana use for males, with no effect on tobacco use.…”
Section: Mexican Middle School Adaptationsmentioning
confidence: 99%
“…The results of the current study are consistent with others found in other Spanish-speaking contexts. The desired effects of Mantente REAL on preventing alcohol use were also obtained in Mexico (Marsiglia et al, 2015), Uruguay (Marsiglia et al, 2018), and Mexican American youth, especially when the program was adapted to Latino populations (Kulis et al, 2005). This result suggests that the degree to which the curriculum is culturally adapted can affect the program's effectiveness, as previous meta-analytic research has indicated (Griner & Smith, 2006).…”
Section: Discussionmentioning
confidence: 59%
“…Several studies have demonstrated the significant effects of Mantente REAL in reducing adolescent substance use (alcohol, tobacco, and cannabis), preserving or increasing negative attitudes towards substance use, strengthening norms against substance use, and increasing the use of effective drug resistance strategies (Kulis et al, 2005;Kulis et al, 2019;Marsiglia et al, 2015). As regards gender differences in the effectiveness of Mantente REAL, previous research conducted in Mexico indicated that although gender differences in adolescent alcohol use have narrowed to near parity the effects of the program on alcohol frequency are moderated by gender, with females showing stronger desired effects than shown by males (Marsiglia et al, 2015). Despite the evidence in other Spanish-speaking contexts, no research has previously tested the effectiveness of the Spanish version of Mantente REAL adapted to Spain.…”
Section: Mantente Real As An Effective Prevention Programmentioning
confidence: 99%
“…These themes are worked with the school community through strategies that address the continuous clinical follow-up of learners 25 - 26 , 30 - 31 , 46 - 47 , 63 , 74 , 98 -95, 108 , 132 , through activities to prevent health problems 52 , 68 , 90 , 92 , 97 , 126 , availability of resources in school spaces as a way of encouraging changes in habits 15 , 19 , 27 , 54 , 71 , 100 , 121 - 122 , 129 , educational activities with students and other members of the school community (14-24,27-29,32-45,49-51,53-62,64-67,69-73,75-77, 79-89,91,93,98-107,109- 125,127-131,133-134) and group activities 96 .…”
Section: Resultsmentioning
confidence: 99%